Pengaruh Manajemen Laba Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderasi - Angelita Angelita; Randy Kuswanto (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study examines whether profitability moderates the relationship between earnings management and firm value. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange during 2022–2023. A quantitative approach was applied using Moderated Regression Analysis (MRA) and secondary data from annual financial reports. The final sample includes 344 companies per year, selected through purposive sampling. The results show that earnings management has no significant effect on firm value. In contrast, profitability measured by Return on Assets (ROA) has a positive and significant effect. The interaction between earnings management and ROA shows a significant negative effect, indicating that profitability weakens the relationship between earnings management and firm value. These findings suggest that the market values solid financial performance more than manipulative earnings signals.